Resveratrol Upregulates mmu-miR-363-3p via the PI3K-Akt Pathway to Improve Insulin Resistance Induced by a High-Fat Diet in Mice - Shu L (Dove Medical Press, 2020)
Linyi Shu, 1, 2 Hang Zhao, 2 Wenli Huang, 1, 2 Guangsen Hou, 1, 2 Guangyao Song, 1, 2 Huijuan Ma 1–3 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei 050017, People’s Republic of China; 2Endocrinology Department, Hebei General Hospital, Shijiazhuang, Hebei 050051, People’s Republic of China; 3Hebei Key Laboratory of Metabolic Diseases, Hebei General Hospital, Shijiazhuang, Hebei 050051, People’s Republic of ChinaCorrespondence: Guangyao SongEndocrinology Department, Hebei General Hospital, 348, Heping West Road, Shijiazhuang, Hebei 050051, People’s Republic of ChinaTel +86 311 8598 8556Email guangyaosong123@163.comPurpose: This study aimed to investigate how resveratrol (RSV) improves high-fat diet (HFD)-induced hepatic insulin resistance in mice via microRNA (miRNA) mmu-miR-363-3p in vitro and in vivo.Materials and Methods: C57BL/6J mice were fed a HFD for 8 weeks to establish an insulin resistance model. The model mice were treated or not with RSV for 6 weeks. Differential miRNA expression in mouse liver tissues was analyzed by high-throughput sequencing. Mouse HepG2 cells were treated with palmitic acid (PA) to establish a cell model of insulin resistance. HepG2 cells were transfected with mmu-miR-363-3p inhibitor or mimic, and the expression of PI3K-Akt signaling pathway-related proteins was analyzed.Results: Based on the high-throughput sequencing analysis, mmu-miR-363-3p was identified as a major miRNA involved in the action of RSV on insulin resistance. Based on KEGG pathway enrichment analysis, PI3K-Akt signaling was found to be significantly enriched among differentially expressed miRNAs, and this pathway is closely related to insulin resistance. RSV treatment reduced the expression of FOXO1 and G6PC, which are downstream of the PI3K-Akt pathway. In the cell model, mmu-miR-363-3p inhibitor significantly suppressed p-Akt and p-PI3K levels, but enhanced those of FOXO1 and G6PC. In contrast, mmu-miR-363-3p mimic significantly enhanced the p-Akt and p-PI3K levels, but suppressed FOXO1 and G6PC expression, which was similar to the effect of RSV.Conclusion: RSV improves insulin resistance by upregulating miRNA mmu-miR-363-3p via the PI3K-Akt pathway.Keywords: insulin resistance, resveratrol, microRNA, high-throughput sequencing, PI3K-Akt pathway